2013
DOI: 10.1088/0953-2048/26/8/085002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of filter shapes on the capture efficiency of a superconducting high-gradient magnetic separation system

Abstract: This paper reports experimental and analytical studies on the capture efficiency of a superconducting high-gradient magnetic separation (HGMS) system, employing ferromagnetic filters with various wire diameters and packing fractions. The magnetization force was inversely proportional to wire diameter because the magnetic field gradient increased with decreasing wire diameter. In addition, the capture efficiency of the HGMS system was increased with decreasing wire diameter and increasing packing fraction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Figure 5 shows axial velocity profiles and particle trajectories depending on magnetized wire thickness: 20 mm to 300 mm, corresponding to Filters 1»5 in Table 1 (rB) was found different from wire thickness (Kim et al 2013). A thick wire certainly provides with less gradient.…”
Section: Effect Of Mesh Filter Configurationmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 5 shows axial velocity profiles and particle trajectories depending on magnetized wire thickness: 20 mm to 300 mm, corresponding to Filters 1»5 in Table 1 (rB) was found different from wire thickness (Kim et al 2013). A thick wire certainly provides with less gradient.…”
Section: Effect Of Mesh Filter Configurationmentioning
confidence: 96%
“…Magnetic force has been used to separate and direct ferromagnetic particles in applications in various fields, such as biology, biochemistry, medicine, and environmental science (Schaller et al 2008;Kim et al 2013;Zadravec et al 2014). In wastewater treatment, various superconducting magnets have long been employed to enhance the filtration performance of ferromagnetic filters (Bitton et al 1974;Latour and Kolm 1976;Allen et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Baik calculated the magnetic field distribution around circular stainless steel matrix via finite element analysis and found that the magnetic force acting on a particle is in average 160 times larger than that only via solenoid magnet [13]. Kim reported the studies on the capture efficiency of a HGMS system employing ferromagnetic matrices with various diameters and packing fractions [14]. The magnetic forces are calculated by computing the magnetic flux density and the gradient with finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, matrices of different size or shapes, different arrangements were manufactured to do experiments to optimize the HGMS system (Too et al, 1986;Badescu et al, 1996;Ebner et al, 2007;Kim et al, 2013;Padmanabhan and Sreenivas, 2011;Chen et al, 2014). However, as there are so many factors influencing the recovery efficiency, the quantitative analyses of these factors were not done systematically.…”
Section: Introductionmentioning
confidence: 99%